2022
DOI: 10.1038/s42949-022-00078-6
|View full text |Cite
|
Sign up to set email alerts
|

Promoting economic and environmental resilience in the post-COVID-19 era through the city and regional on-road fuel sustainability development

Abstract: How to control the global temperature rise within 1.5 °C in the post-COVID-19 era has attracted attention. Road transport accounts for nearly a quarter of global CO2 emissions, and the related sulfur dioxide (SO2) emissions also trigger air pollution issues in population-intensive cities and areas. Many cities and states have announced a timetable for phasing out urban-based fossil fuel vehicles. By combining a Markov-chain model with a dynamic stochastic general equilibrium (DSGE) model, the impacts of on-roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…One possible reason may be that the environmental costs associated with carbon emissions, such as pollution and climate change, pose risks to economic stability and sustainability. Studies have shown that the negative externalities of carbon emissions can lead to increased resource scarcity, regulatory burdens, and potential disruptions to industries and supply chains [81][82][83]. Furthermore, moving toward a low-carbon economy and the adoption of sustainable practices have been identified as crucial factors for enhancing economic resilience in the face of environmental challenges.…”
Section: The Effects Of Digital Economy On Economic Resiliencementioning
confidence: 99%
“…One possible reason may be that the environmental costs associated with carbon emissions, such as pollution and climate change, pose risks to economic stability and sustainability. Studies have shown that the negative externalities of carbon emissions can lead to increased resource scarcity, regulatory burdens, and potential disruptions to industries and supply chains [81][82][83]. Furthermore, moving toward a low-carbon economy and the adoption of sustainable practices have been identified as crucial factors for enhancing economic resilience in the face of environmental challenges.…”
Section: The Effects Of Digital Economy On Economic Resiliencementioning
confidence: 99%